Comparison of Crosslinking Efficiency in Dip and Roll-Deposited Coatings on Their Oxygen Barrier - Ben Dhieb, Fatma (ACS Omega, 2019)
[Image: see text] Coating techniques are key factors in determining coated film properties. In the present study, nanocomposite coatings of poly(vinyl alcohol) and a nanoclay, montmorillonite, were deposited layer-by-layer using roll (doctor blade, DB) and dip coating techniques, in an effort to compare the impact of these techniques on the crosslinking efficiency and oxygen barrier of the coated films. The barrier properties at different relative humidities were tested, and the extent of nanoclay intercalation as well as the films’ morphology was investigated. Barrier was further improved by crosslinking the coating with glyoxal and glutaraldehyde. Both techniques gave similar results but with a higher impact of relative humidity in roll coated films. Better results were achieved by tailoring the composition of those coatings to favor a higher density of hydrogen bonding in the coating.